EXPRESSIVE WRITING THERAPY UNTUK MENINGKATKAN KEMAMPUAN PENGUNGKAPAN DIRI (SELF DISCLOSURE) PADA PASIEN SKIZOFRENIA PARANOID - Chairun Nisaa’; Fitriatul Masruroh; Herlan Pratikto (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
Schizophrenia is a psychotic disorder characterized by major disturbances in the mind, emotions, and disturbed mind-behavior. Schizophrenia disorder is divided into 3 types, namely disorganized, catatonic and paranoid schizophrenia. The main feature of paranoid type schizophrenia is the focus on one or more delusions that include greatness, persecution, jealousy, anxiety, or confusion in the absence of evidence. The focus of this study is the provision of interventions in the form of expressive writing therapy to improve self-disclosure to one of the paranoid schizophrenia patients at RSJ Menur Surabaya. The study was conducted for 5 weeks with details of 3 weeks of psychological assessment and 2 weeks of psychological intervention. The methods used in research are qualitative with a case study approach. The results of this study indicate that expressive writing therapy is effectively used as a medium to express the feelings/emotions of the Subject.